2020
DOI: 10.3390/app10103579
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Optimization of White LED Based on Mesopic Luminance and Color Gamut Volume for Dim Lighting Conditions

Abstract: The study aims to propose an approach of white LED spectral optimization based on mesopic luminance and color gamut volume for dim lighting conditions. Three optimal white LED spectra with relatively higher mesopic luminance and color gamut volume, the highest mesopic luminance, and the largest gamut volume are recommended for reducing energy consumption and enhancing color perception and recognition of human eyes. The theoretical simulation shows that the spectra with higher correlated color temperatures (CCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This was a claimed advantage during the transition process from high-pressure sodium to white light-emitting diode (LED) light sources a decade ago. Many works have been dedicated to optimizing high mesopic efficiency light sources [14][15][16]. Although mesopic vision applications in road lighting have been widely accepted, Gibbson et al's work showed that there are no significant differences in the detection distances for high and low correlated color temperature (CCT) sources when the speed is over 56 km/h [17].…”
Section: Introductionmentioning
confidence: 99%
“…This was a claimed advantage during the transition process from high-pressure sodium to white light-emitting diode (LED) light sources a decade ago. Many works have been dedicated to optimizing high mesopic efficiency light sources [14][15][16]. Although mesopic vision applications in road lighting have been widely accepted, Gibbson et al's work showed that there are no significant differences in the detection distances for high and low correlated color temperature (CCT) sources when the speed is over 56 km/h [17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to previous spectral optimisation studies [6,58,[60][61][62][63]100,101,[115][116][117][118], this work provides at the authors' best knowledge one of the most comprehensive multichannel LED datasets for metamer spectra. More advanced analyses between additional colour quality metrics are possible with the optimised spectra, which we did not fully exploit.…”
Section: Discussionmentioning
confidence: 99%
“…The illuminance value presented in the upperleft corner can be derived by calculating the area under the curve within the wavelength range of 390-830 nm. This range is also referred to as the CIE 2008 photopic luminous efficiency function (E(λ)), which represents the average spectral sensitivity of human vision to light [45]. Thus, effective conversion would enable the use of a spectrometer to evaluate photovoltaic performance under low-illuminance conditions.…”
Section: Experimental and Validation Proceduresmentioning
confidence: 99%